2019
DOI: 10.1177/2042018819828217
|View full text |Cite
|
Sign up to set email alerts
|

Economics of gastroenteropancreatic neuroendocrine tumors: a systematic review

Abstract: Background: Despite current interest, enthusiasm and progress in the development of therapies for gastroenteropancreatic (GEP) neuroendocrine tumors (NETs), there are substantial gaps in the published literature regarding cost-of-illness analyses, economic evaluation and budget impact analyses. Compounding the issue is that data on resource utilization and cost-effectiveness of different diagnostic and therapeutic modalities for GEP-NETs are scarce. Methods: A systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 40 publications
(76 reference statements)
0
13
0
1
Order By: Relevance
“…It was stated in the review by Chau et al [9] that "Although the published literature in the area of NET is substantial, there is a lack of treatment-specific and comparative economic and outcomes research data associated with commonly used treatments". In a subsequent review in 2019 Grande et al [21] suggested "further economic evaluations are required to inform healthcare decision-making". Our review demonstrates health economic literature in NEN which fulfils quality criteria for HEEs is still scarce.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was stated in the review by Chau et al [9] that "Although the published literature in the area of NET is substantial, there is a lack of treatment-specific and comparative economic and outcomes research data associated with commonly used treatments". In a subsequent review in 2019 Grande et al [21] suggested "further economic evaluations are required to inform healthcare decision-making". Our review demonstrates health economic literature in NEN which fulfils quality criteria for HEEs is still scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Papers published from 2010 to October 2019 in English were included. We looked at treatment search terms, taking into account terms used in previous reviews by Chau et al [9] and Grande et al [21] (Table 4). See Appendix 1 for full search strategy terms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These metabolically active substances can be reason for patients to present themselves to a physician, but the majority of neuroendocrine tumors are non-functioning [ 8 ], although the resulting “carcinoid syndrome” of metabolically functional neuroendocrine tumors with an incidence of 19% is a common sign of the disease and is associated with flushing and diarrhea [ 1 , 9 ]. Other potential diseases associated with NETs are Zollinger–Ellison syndrome, hypoglycemia and bronchospasm [ 10 ]. The term of neuroendocrine carcinoma (NEC) has also been proposed for the poorly differentiated neuroendocrine neoplasms (NEN), as opposed to the well-differentiated neuroendocrine tumors (NET), and efforts are being made to uniformize the nomenclature, e.g., by the International Agency for Research on Cancer—World Health Organization (IARC-WHO) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing role of PET/CT imaging for neuroendocrine neoplasms, especially using SSR targeted tracers, is generally reflected by an increasing implementation and appreciation of PET/CT imaging in national and international guidelines on NETs [ 9 , 27 , 28 ]. Yet high diagnostic costs and the resulting financial burden in the context of the increasing incidence of NETs have increased the need for an additional evaluation of the diagnostic modalities from a cost-effectiveness perspective [ 10 ]. In our analysis we focus on two of the most common and widely available tracers for each modality: 68 Ga-DOTA-TATE for PET/CT imaging and 111 In-pentetreotide for SPECT/CT imaging.…”
Section: Introductionmentioning
confidence: 99%